A new electron diffraction approach for structure refinement applied to Ca3Mn2O7. Issue 3 (17th March 2021) - Beanland, R.; Smith, K.; Vaněk, P.; Zhang, H.; Hubert, A.; Evans, K.; Römer, R. A.; Kamba, S.
Abstract : The `digital' large‐angle convergent‐beam electron diffraction (D‐LACBED) method uses computer control of a transmission electron microscope to collect hundreds of diffraction patterns from a region a few nanometres in size, which are combined into a single data set. The sensitivity of the resulting patterns to crystal structure is explored using the Ruddlesden–Popper oxide Ca3 Mn2 O7 and it is found that refinement of atomic coordinates can be performed to sub‐picometre precision. Abstract : The digital large‐angle convergent‐beam electron diffraction (D‐LACBED) technique is applied to Ca3 Mn2 O7 for a range of temperatures. Bloch‐wave simulations are used to examine the effects that changes in different parameters have on the intensity in D‐LACBED patterns, and atomic coordinates, thermal atomic displacement parameters and apparent occupancy are refined to achieve a good fit between simulation and experiment. The sensitivity of the technique to subtle changes in structure is demonstrated. Refined structures are in good agreement with previous determinations of Ca3 Mn2 O7 and show the decay of anti‐phase oxygen octahedral tilts perpendicular to the c axis of the A 21 am unit cell with increasing temperature, as well as the robustness of oxygen octahedral tilts about the c axis up to ∼400°C. The technique samples only the zero‐order Laue zone and is therefore insensitive to atom displacements along the electron‐beam direction. For this reason it is not possible to distinguish between in‐phase and anti‐phase oxygen octahedral tilting about the c axis using the [110] data collected in this study.